LA REFORMA ENERGÉTICAY SU IMPACTO EN UN ORGANISMO DESCENTRALIZADO EL CASO DE LA COMISIÓN FEDERAL DE ELECTRICIDAD - Juan Alfredo Lino Gamiño; Salvador López Reyes; Sergio Felipe López Jiménez; Sergio Iván Ramírez Cacho (European Scientific Journal, ESJ, 2014)
The aim of this paper is to analyze the impact of energy reform in the company of Mexican government, Federal Electricity Commission, on the assumption of changes in structural reforms, in particular energy, which has a high impact on changing the Federal Electricity Commission, as productive enterprise and business unit. Does the energy reform achieved transform the CFE as productive enterprise?). How will impact the end user change the CFE to be a public body to productive enterprise and business unit? The research method is descriptive and analytical from theoretical and methodological approach. Finally, the analysis of the impact of the reform is to totally transform CFE and position as a prolific enterprise.